Social Media, Impact on Student Learning Behavior - Kurniawan, Yulius; Lee, Abram Scott; Khayru, Rafadi Khan; Hariani, Mila (Metromedia, 2022)
Social media is a medium on the internet that allows users to represent themselves and interact, collaborate, share, communicate with other users, and form virtual social bonds. A common characteristic of every social media is the openness of dialogue between users. Social media has positive and negative impacts on students. This paper will review the role of social media on student learning behavior.